2014
DOI: 10.1177/0267659114558287
|View full text |Cite
|
Sign up to set email alerts
|

Coronary collateral circulation in patients with chronic coronary total occlusion; its relationship with cardiac risk markers and SYNTAX score

Abstract: Cardiac risk markers, such as NT-proBNP, hs-cTnT and hs-CRP are independently associated with CCC in stable coronary artery disease with chronic total occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Atherosclerotic plaque localizations have a linear relation with the blood viscosity that frequent plaque formation were observed among the higher viscosity regions especially in the proximal segments of the coronary arteries 22). Börekçi et al observed higher SYNTAX scores in patients with poor CCC 20). Similarly, we observed that in the poor CCC group, SYNTAX scores were significantly higher compared to good CCC group.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Atherosclerotic plaque localizations have a linear relation with the blood viscosity that frequent plaque formation were observed among the higher viscosity regions especially in the proximal segments of the coronary arteries 22). Börekçi et al observed higher SYNTAX scores in patients with poor CCC 20). Similarly, we observed that in the poor CCC group, SYNTAX scores were significantly higher compared to good CCC group.…”
Section: Discussionsupporting
confidence: 71%
“…Angiogenesis (new vessel formation) and/or arteriogenesis (growth of preexisting arterioles) result in the CCC development. Although, in the previous reports, the role of hemorheological and biochemical factors in the development CCC has been recognized,19)20) the effect of the WBV on CCC has not been studied well. The present study showed that patients with poor CCC had significantly higher WBV values for both shear rates compared to the good collateral group, and higher WBV was an independent predictor for poor CCC.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recently, MPV has not been found to be associated with coronary collateral circulation in stable CAD with chronic total occlusion. 23 Plateletcrit is a measure of total platelet mass (PCT = platelet count × MPV / 10 7 ). Recently, the prognostic role of the plateletcrit was shown in 2572 STEMI patients undergoing PPCI.…”
Section: Discussionmentioning
confidence: 99%
“…28 The diabetic pathophysiology promotes an anti-angiogenic process and meanwhile mitigates pro-angiogenic factors in coronary vasculature during ischemia, jointly leading to impaired collateral growth. 28,29 Although the influence of the DM on collateral development is debatable, 11,[30][31][32][33][34] it has been reported that diabetics and prediabetics generally have a poor acute collateral response because of the diffusely impaired endothelial function, [35][36][37] particularly in the presence of active smoking. 5,38,39 Whereas the DM and prediabetes aggressively induces atherosclerosis and may be more susceptible to infarction; they can also activate some endogenous cardioprotective mechanisms protecting the left ventricular contractile function.…”
Section: Discussionmentioning
confidence: 99%